Inter‐embodiment and the experience of genetic testing for familial hypercholesterolaemia. Issue 4 (16th August 2012) - Jenkins, Nicholas; Lawton, Julia; Douglas, Margaret; Hallowell, Nina
Abstract In this article we explore the concept of inter‐embodiment and its potential for advancing sociological research into illness biography and genetic identity. Inter‐embodiment theory views embodied knowledge as produced through relations between bodies, as opposed to originating from within the body or as the product of relations between disembodied selves. Drawing on a qualitative study in which we interviewed 38 individuals about their experiences of discovering they had high cholesterol and undergoing genetic testing for familial hypercholesterolaemia (FH), we discuss how their narratives may be understood from an inter‐embodiment perspective. The participants frequently talked at length about their family histories of high cholesterol and cardiovascular disease. Through these accounts, we develop the concept of the family corpus in order to highlight the role body networks play in shaping lay constructions of genetic identity and a familial disease biography. The notion of a family corpus, we argue, is useful in understanding why genetic testing for FH was experienced as either biographical re‐enforcement or as biographical disruption. We conclude by discussing the implications of our findings for future sociological research into illness biography and genetic identity.